Designing and Migration of Library Database - K, Sathiyapriya; S, Bhavadharinie; R, Atchaya; H, Kripaa; V, Sowmya (Journal of Trends in Computer Science and Smart Technology, 2023)
Library Management System is the finest tool for automating libraries in India. Data migration from such proprietary applications is difficult. In the majority of the current libraries, the tabular bibliographic data is exported to spreadsheet forms like CSV and XLSX. It is necessary to transform bibliographic information from spreadsheet format to the industry-standard MARC 21 format. MARC tags are applied to bibliographic information in spreadsheets using MARC Edit software. The .xlsx file is converted to .txt (tab delimited) which is then converted to .mrk format. Next, the .mrk file is changed to .mrc file. Processes for data mapping are necessary prior to this move. Later, the .mrc file must be loaded into a MySQL-compatible open source database. To achieve that, the migrated material needs to be properly validated. Therefore, it is crucial to use accurate data mapping when converting data from XLSX format to MARC 21 format. Following the importation into a database, users can obtain data for cataloguing and visualisation for easy understanding. Projects using open-source software are fundamentally about cooperation and transparency, and many eminent Indian institutions have switched to these open source platforms.